The potential role of nanobodies in asthma therapy - Baraa Khalid Salah Al-Sheakly; Fatemeh Saheb Sharif-Askari; Fatemeh Saheb Sharif-Askari; Narjes Saheb Sharif-Askari; Narjes Saheb Sharif-Askari; Jennifer E. Hundt; Rabih Halwani; Rabih Halwani (Frontiers in Pharmacology)
Asthma is a chronic inflammatory disease of the airways characterized by bronchoconstriction, airway hyperresponsiveness, and mucus production. The pathophysiology of asthma involves a complex interplay of immune cells and mediators, including cytokines, chemokines, and other inflammatory molecules. Despite advances in asthma management, many patients continue to experience symptoms due to the limitations of current therapies. Monoclonal antibodies (mAbs) targeting specific inflammatory mediators have improved treatment outcomes for some patients, but challenges such as poor tissue penetration and high costs remain. Nanobodies (Nbs), a novel class of single-domain antibodies, offer a promising alternative due to their small size, stability, and potential for enhanced tissue penetration. This review discusses the key mediators involved in asthma, challenges in current treatments, and the potential of Nbs as a new therapeutic strategy. We also explore current studies and innovations in nanobody technology.